2015
DOI: 10.5539/ep.v5n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Health Hazards of Low-Quality Irrigation Water in Vegetable Production in Morogoro, Tanzania

Abstract: This study assessed the perceptions of vegetable farmers, traders, consumers and key informants on the health hazards of using low-quality water in irrigation vegetable production in Morogoro, Tanzania. Methods used to collect data were a survey involving all farmers in Changarawe village and Fungafunga area using low-quality water for irrigation vegetable production (n=60), consumers of low-quality water irrigated vegetables (n=70) and vegetable traders selling low-quality water irrigated vegetables (n=60), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Due to poor sanitation, lack of proper drainage system and lack of wastewater treatment plant, effluent from industries and domestic sewage is often discharged into streams, rivers and open gutters 14 . It is estimated that about 47% of households discharge their liquid waste into open gutters 20 . Farmers in both urban and city peripheries make use of wastewater for vegetable irrigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to poor sanitation, lack of proper drainage system and lack of wastewater treatment plant, effluent from industries and domestic sewage is often discharged into streams, rivers and open gutters 14 . It is estimated that about 47% of households discharge their liquid waste into open gutters 20 . Farmers in both urban and city peripheries make use of wastewater for vegetable irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…According to 20 , the quality of the water use for vegetable irrigation in urban cities of Ghana is noted to be poor and below standards 23 . Antwi-Agyei reported that 160 irrigation water and 163 soil samples, 93% and 91% had levels of E. coli , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, whereas earlier studies such as Parada et al (2021) appear to support increasing use of rain‐fed agriculture in urban cities, others such as Bougnom and Piddock (2017), Miller‐Robbie et al (2017) and Haldar et al (2021) argue for wastewater because of its potential benefits for urban agriculture. However, recent studies have raised concerns about the quality of wastewater in urban agriculture based on their discoveries of harmful organisms in wastewater used by urban farmers (Abdallah & Mourad, 2021; Amuah et al, 2022; Mayilla et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In Ghana, studies on the quality of water used for irrigation for vegetable and crop production in general have indicated different forms of contamination (Abdallah & Mourad, 2021; Amuah et al, 2022; Mayilla et al, 2015). There are the same indications in studies conducted in Cote D'Ivoire (Kambire et al, 2022; Koffi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…According to Valipour and Singh (2016), studies on irrigation with treated wastewater have been conducted on other aspects such as soil, ground water, crops, health, irrigation equipment and other environmental issues with limited studies on management. In Tanzania for instance, recent studies concentrated much on the health and socio-economic issues related to the use of LQW (Kilobe et al, 2013;Nyomora, 2015;Mayilla et al, 2015, Msigala et. al.…”
Section: Introductionmentioning
confidence: 99%